Software Architecture with C : Design modern systems using effective architecture concepts, design patterns, and techniques with C++20 /: Design modern systems using effective architecture concepts, design patterns, and techniques with C++20. (2021) - Ostrowski, Adrian; Gaczkowski, Piotr
No abstract available